Comparison of Efficacy and Safety of Midazolam versus Nitrous Oxide as Sedative Agents during Paediatric Dental Treatment: A Systematic Review - Palak Janiani; Deepa Gurunathan (Association of Support to Oral Health Research (APESB), 2024)
Objective: To identify and study the existing literature on the efficacy and safety of midazolam compared to inhalation of nitrous oxide in children undergoing dental treatment. Material and Methods: Electronic resources such as PubMed Central, Cochrane Database of Systematic Reviews, Lilacs, Science Direct, and SIGLE were thoroughly searched. The title scan was used to find randomised controlled trials reviewed for inclusion by reading the abstract. Studies comparing the sedative, behavioural, and anxiolytic effects and safety in children undergoing dental treatment under midazolam and nitrous oxide inhalation were included. The Cochrane Reviews system software, Revman 5.4.1, was used to assess the quality of the included studies. Results: 11328 articles were identified by screening the electronic databases, of which 10906 were eliminated after titles were read and duplicates were removed. Ten full-text articles were examined, of which three were excluded as they did not match the eligibility criteria. Hence, a total of 7 studies were included. Midazolam and nitrous oxide inhalation were not statistically different in terms of the success of treatment and behaviour modification. However, midazolam showed a deeper level of sedation and resulted in amnesia in more children when compared to nitrous oxide sedation. All of the included studies were found to have a high risk of bias. Conclusion: Though all the studies included showed an increased risk of bias, midazolam and nitrous oxide inhalation seem equally effective sedative agents for controlling behaviour in children undergoing dental treatment. Midazolam shows a deeper sedation level when given orally and produces a higher rate of anterograde amnesia.